Suicidal Ideation Among Children and Young Adults in a 24/7 Messenger-Based Psychological Chat Counseling Service - Kohls, Elisabeth; Guenthner, Lukas; Baldofski, Sabrina; Eckert, Melanie; Efe, Zeki; Kuehne, Katharina; Saee, Shadi; Thomas, Julia; Wundrack, Richard; Rummel-Kluge, Christine (Frontiers in Psychiatry, 2022)
Suicidality in children and young adults is a pervasive problem: approximately 40% of respondents in epidemiological surveys in German schools reported suicidal ideation, while up to 9% reported a suicide attempt in the past. While there is compelling evidence for the effectiveness of telephone-based hotline services, an increasing preference of adolescents for messenger-based counseling services can be observed. Therefore, the present study aims to investigate the utilization behavior and user satisfaction of users contacting a German messenger-based chat counseling service (“krisenchat”) regarding suicidal ideation. The present cross-sectional study analyzed retrospective anonymous data on sociodemographic variables, utilization behavior, and user satisfaction of krisenchat users who used the service between May 2020 and July 2021. Chi-square-tests were used to identify associations of sociodemographic characteristics and utilization behavior with suicidal ideation. Mann-Whitney-U-tests were used to compare the user satisfaction and the recommendation-to-others-rate between suicidal and non-suicidal krisenchat-users. In total, chat data of N = 11,031 users were collected. Of the n = 6,962 users included in the final analysis, n = 1,444 (20.7%) contacted krisenchat because of suicidal ideation. The average user experiencing suicidal ideation was 17 years old, female and currently not receiving other treatment. Further, suicidal ideation was significantly and positively associated with age and non-suicidal self-injury. Regarding utilization patterns, there were significant positive associations between suicidal ideation and counseling session count, mean amount of messages sent, and mean amount of words used per message by the user. User satisfaction was high, with 64.7% (n = 413) of users that answered the feedback survey and experiencing suicidal ideation rating the help they received as at least ‘good’ and a recommendation rate of 89.6% (n = 571). Most importantly, no differences were found between users reporting suicidal ideation and those that do not regarding satisfaction and the probability of recommending the service. Results imply satisfaction with the counseling service among users with suicidal ideation. Nevertheless, there is a need for further research into messenger-based counseling services regarding the prevention of suicidal behavior in children, youths and young adults. Longitudinal studies are especially needed to assess the effectiveness of messenger-based interventions.